2015
DOI: 10.4187/respcare.04348
|View full text |Cite
|
Sign up to set email alerts
|

FEV1/FEV6in Primary Care Is a Reliable and Easy Method for the Diagnosis of COPD

Abstract: BACKGROUND: FEV 6 can be used as a convenient alternative to FVC. The aim of this study was to determine an alternative to the fixed cutoff points of FEV 1 /FVC <0.70 suitable for FEV 1 /FEV 6 in primary care. METHODS: Pulmonary function testing was conducted on volunteers recruited from 4 community centers in Xi'an, China, between July and August 2012. Participants underwent 3 FVC maneuvers. The maneuver with the best FEV 1 was retained. FVC, FEV 1 , and FEV 6 were measured by portable spirometer. The receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…We also tested the validity of a suggested FEV 1 /FEV 6 <0.72 cut-off for airway limitation reported in studies conducted in Japan and China. [ 23 , 24 ] We chose this value among others because of the similar ethnicity between these and our study population, which is an important consideration for evaluating pulmonary function. [ 25 ] Using this cut-off for our study population, sensitivity was 45.5%, specificity was 89.3%, PPV was 57.1%, and NPV was 83.9%.…”
Section: Discussionmentioning
confidence: 99%
“…We also tested the validity of a suggested FEV 1 /FEV 6 <0.72 cut-off for airway limitation reported in studies conducted in Japan and China. [ 23 , 24 ] We chose this value among others because of the similar ethnicity between these and our study population, which is an important consideration for evaluating pulmonary function. [ 25 ] Using this cut-off for our study population, sensitivity was 45.5%, specificity was 89.3%, PPV was 57.1%, and NPV was 83.9%.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to those of the present study. Although FEV 6 is an acceptable surrogate for FVC in spirometry, FEV 6 has some drawbacks, such as the underestimation of mild airway obstruction [ 30 , 31 , 32 ]. Hernández et al reported that FEV 1 /FVC values of <0.7 determined using a smartphone-based spirometer, namely Air-Smart, for detecting obstructive airway diseases had a sensitivity of 94.0% and a specificity of 97.2% [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the cigarette-dependence status, two groups of participants were identified: nondependent (FTCD score ≤ 2) and dependent (FTCD score ≥ 3). For the spirometry test, three spirometric patterns were possible 43 : “no” bronchial obstruction (FEV 1 /FEV 6 ≥ 0.80), “possible” bronchial obstruction (0.70 ≤ FEV 1 /FEV 6 < 0.80) and “most likely” bronchial obstruction (FEV 1 /FEV 6 < 0.70). According to the SLA values, two scenarios arise.…”
Section: Population and Methodsmentioning
confidence: 99%